2007
DOI: 10.1371/journal.ppat.0030177
|View full text |Cite
|
Sign up to set email alerts
|

Chronic HIV-1 Infection Frequently Fails to Protect against Superinfection

Abstract: Reports of HIV-1 superinfection (re-infection) have demonstrated that the immune response generated against one strain of HIV-1 does not always protect against other strains. However, studies to determine the incidence of HIV-1 superinfection have yielded conflicting results. Furthermore, few studies have attempted to identify superinfection cases occurring more than a year after initial infection, a time when HIV-1-specific immune responses would be most likely to have developed. We screened a cohort of high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
188
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(206 citation statements)
references
References 52 publications
12
188
1
5
Order By: Relevance
“…HIV-1 envelop (env) V1-V5 gene region was amplified by performing high-fidelity nested PCR using an EasyA kit (Stratagene). The primers used were as follows: round 1 (product size 1415 bp), forward 59-TTGCAATAGAAAAATTCTCCTC-39, and reverse 59-CCTGGTGGGTGCTACTCCTA-39); round 2 (product size 1098 pb), forward 59-CCATGTGTAAAGTTAACCCC-39, and reverse, 59-ATGAGGGACAATTGAGAAGTGTCTAG-39; PCR condition as described in (27). Amplicons were purified by using a high pure PCR product purification kit (Roche), and cloned into the TA cloning vector provided in a TOPO TA cloning kit (Invitrogen) in accordance with the manufacturer's instructions.…”
Section: Hiv-1 Env Sequencing and Analysismentioning
confidence: 99%
“…HIV-1 envelop (env) V1-V5 gene region was amplified by performing high-fidelity nested PCR using an EasyA kit (Stratagene). The primers used were as follows: round 1 (product size 1415 bp), forward 59-TTGCAATAGAAAAATTCTCCTC-39, and reverse 59-CCTGGTGGGTGCTACTCCTA-39); round 2 (product size 1098 pb), forward 59-CCATGTGTAAAGTTAACCCC-39, and reverse, 59-ATGAGGGACAATTGAGAAGTGTCTAG-39; PCR condition as described in (27). Amplicons were purified by using a high pure PCR product purification kit (Roche), and cloned into the TA cloning vector provided in a TOPO TA cloning kit (Invitrogen) in accordance with the manufacturer's instructions.…”
Section: Hiv-1 Env Sequencing and Analysismentioning
confidence: 99%
“…In a recent study by Piantadosi et al, of seven dually infected Kenyan women, only one individual was found to harbor a virus that was a recombinant of the parental viruses (subtypes A and D) in the V1V5 region of env. 3 This virus was found in the minority of sequences at 73 days postinfection but absent for the next 4.5 years until its reappearance as a 25% proportion of env sequences. 3 In a study by Gerdhart et al that analyzed the vpu=gp120 region of env sequences from specimens obtained at 3-month intervals from a subject triply infected by two strains of subtype A and a subtype C virus, exhibiting symptoms of late-stage disease, env analysis identified several URFs; however, these recombinants always comprised a small minority (<1%) of the viral quasispecies in the individual at each of the time points analyzed.…”
mentioning
confidence: 95%
“…3 This virus was found in the minority of sequences at 73 days postinfection but absent for the next 4.5 years until its reappearance as a 25% proportion of env sequences. 3 In a study by Gerdhart et al that analyzed the vpu=gp120 region of env sequences from specimens obtained at 3-month intervals from a subject triply infected by two strains of subtype A and a subtype C virus, exhibiting symptoms of late-stage disease, env analysis identified several URFs; however, these recombinants always comprised a small minority (<1%) of the viral quasispecies in the individual at each of the time points analyzed. 11 To best examine the role of sequence identity in the generation of recombinants, individuals dually infected with concordant as well as discordant HIV-1 subtypes must be studied.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, superinfection may be difficult to detect when the superinfecting virus is of the same subtype as the initial virus, and the detection of possible consequent recombinants is restricted to a handful of reports. [2][3][4][5][6] It has previously been reported that superinfection with a virus of different subtype can result in replacement of the original virus. 2,7-9 Fang et al 4 showed replacement of subtype A virus with AC, but did not show the presence of ''pure'' subtype C virus, so the superinfection could have been with an AC recombinant.…”
mentioning
confidence: 99%